The effect of simulated flooding on the structural performance of light frame timber shear walls – An experimental approach. (1st January 2016) - Bradley, A.C.; Chang, W.S.; Harris, R.
Highlights: We test shear walls that have been exposed to simulated flooding. A permanent reduction in mechanical properties is observed. The failure mode of the walls following restoration after flood is altered. Abstract: This paper presents the results of a series of tests on timber shear walls exposed to simulated flooding and drying. Load tests were conducted on three wall types; control, wet and restored. The mechanical properties of each of these wall types were compared. It was found that there were significant losses in mechanical strength for the wet and restored walls tested. For wet walls, ultimate strength was reduced by 20% and for the restored walls ultimate strength was reduced by 25%. The restored walls were observed to fail due to sheathing buckling caused by swelling of the OSB during simulated flooding. This failure mode following flooding and restoration is one that is not currently accounted for by design codes or designers.